Analysis on the performance comparison between a relational database and a non-relational database for big data application - Hasan, Md. Ahsanul; Ahmed, Fardin; Chowdhury, Abul Hossain; Leion, Md. Kamruzzaman; Prince, Md. Rafsan Ferdous (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.